The dynamic response characteristics of traumatic brain injury. (June 2015) - Post, Andrew; Hoshizaki, T.Blaine; Gilchrist, Michael D.; Brien, Susan; Cusimano, Michael; Marshall, Shawn
Highlights: Traumatic brain injury from falls to hard surfaces occur at roughly 4.0 m/s. Traumatic brain injury in this research occurred at levels above 335 g and 23.7 krad/s 2 . Lower responses were required in the antero-posterior impact direction for equivalent types of TBI. Impact location is an important consideration in outcome of a head impact and injury thresholds. Abstract: Traumatic brain injury (TBI) continues to be a leading cause of morbidity and mortality throughout the world. Research has been undertaken in order to better understand the characteristics of the injury event and measure the risk of injury to develop more effective environmental, technological, and clinical management strategies. This research used methods that have limited applications to predicting human responses. This limits the current understanding of the mechanisms of TBI in humans. As a result, the purpose of this research was to examine the characteristics of impact and dynamic response that leads to a high risk of sustaining a TBI in a human population. Twenty TBI events collected from hospital reports and eyewitness accounts were reconstructed in the laboratory using a combination of computational mechanics models and Hybrid III anthropometric dummy systems. All cases were falls, with an average impact velocity of approximately 4.0 m/s onto hard impact surfaces. The results of the methodology were consistent with current TBI research, describing TBI to occur in the range of 335–445 g linear accelerations and 23.7–51.2 krad/s 2 angular accelerations. More significantly, this research demonstrated that lower responses in the antero-posterior direction can cause TBI, with lateral impact responses requiring larger magnitudes for the same types of brain lesions. This suggests an increased likelihood of sustaining TBI for impacts to the front or back of the head, a result that has implications affecting current understanding of the mechanisms of TBI and associated threshold parameters.